Social media engagement and health - Davies, Alisha; Song, Jiao; Sharp, Catherine (International Journal of Population Data Science, 2019)
Main Aim The Digital Health Survey was the first nationally representative survey in Wales aiming to understand the extent to which people use social media, disclose personal health related information through social media sites and different user patterns across population groups. Methods A nationally representative household sample (n=1,252) was identified by a probabilistic sampling approach. One individual, aged 16 years and older, per household was randomly invited to complete a face-to-face questionnaire between April and June 2018. The survey collected quantitative information on use of social media platforms, perception of sharing personal health information on social media platforms, health status and socio-demographic characteristics. We tested the relationships among use, user type, demographics and health status using Chi-squared test or Fisher’s exact test correspondingly. Using estimated marginal means (and 95% confidence intervals), adjusted proportions of people who reported their use on social media platforms was calculated by adjusted mean, controlling for confounders. Results 76.9% of the Welsh population engaged with social media, including 64.7% who used one or more form of social media platform on a daily basis. The most frequently used (i.e. daily) social media platform was Facebook (50.6% of the Welsh population including 23.4% used several times a day). Within the population sampled, controlling for confounders, significant higher proportion of women (91%) users were found compared to men (86%). 99.6% of 16-29 years old used social media with significant lower proportions for older age groups (i.e. 75.6% for 60-69 and 59.8% for 70+). No significant differences were found between social media engagement and deprivation quintiles. 9.6% shared personal health information on social media with friends and family, while only 2.7% shared health information with people they did not know. Conclusion Patterns in social media use are an important consideration for health promotion. The absence of a difference by deprivation groups suggests this approach may reach population more traditional routes have not. However, continued reduction in a digital divide and development of effective solutions for health via social media remains a priority.